Tourism and everyday life in the contemporary city. - (:unkn) unknown (Routledge, 2019)
This book explores the phenomena of the urban everyday and new urban tourism. It provides a systematic framework and draws on a mix of theoretical and empirical work to look at the increasing intermingling of tourists and residents Tourism and urban everyday life are deeply connected in a mutually constitutive way. Tourism has become a key momentum of urban development and affects cities beyond its economic dimension. Urban everyday life itself can turn into a matter of tourist interest for people searching for experiences off the beaten track. Even living in a city as a resident involves moments, activities and practices which could be labelled as touristic . These observations demonstrate some of the various layers in which urban tourism and everyday city life are intertwined. This book gathers multiple interdisciplinary approaches, a diversity of topics and methodological variety to examine this complex relationship. It presents a systematic framework for the dynamic research field of new urban tourism along three dimensions: the extraordinary mundane, encounters and contact zones, and urban co-production.
Keywords: Stadtsoziologie; Tourismus; Alltagsleben; Stadtbewohner; Fremdenverkehr; Stadtentwicklung; Gentrifizierung; Städtetourismus; Freizeitindustrie; Gastronomie; Fremdenverkehrswirtschaft; Reiseverhalten; Sozialer Konflikt; Umgebungslärm; Nutzungskonflikt; Global City; Airbnb; Overtourism; Überforderung